A Study on the Interaction between New Indole Amide Compound and Aluminum(III) Ion. Issue 14 (15th April 2019) - Chen, Jichao; Jiang, Weina; Lu, Wen; Xu, Li; Yang, Shilong; Xue, Huayu; Shi, Jiuzhou; Sun, Xu
Abstract: A new indole‐based compound N‐(pyridine‐2‐ylmethyl)‐1H‐indole‐2‐carboxamide (FL) which could selectively recognize Al 3+ had been designed, synthesized and evaluated. FL could detect Al 3+ with high sensitivity. The fluorescence intensity of FL‐Al 3+ solution was linear dependence to the concentration of Al 3+ in the ranges from 0 to 5 μmol/L. The addition of Al 3+ caused quenching of fluorescence intensity and the limit of detection for Al 3+ was as low as 1.79×10 −9  M. The binding ratio of FL‐Al 3+ was obtained 3:2 by Job's plot and the binding constant was 9.37×10 5 . Moreover, FL had been successfully applied in real sample detection. Abstract : A new indole‐based compound N‐(pyridine‐2‐ylmethyl)‐1H‐indole‐2‐carboxamide (FL) which could selectively recognize Al 3+ had been designed, synthesized and evaluated. With meeting of FL and Al 3+, electron clouds of FL moved to Al 3+ and the coordination reaction took place, which resulted in fluorescence quenching. FL formed a 3:2 bonding ratio with Al 3+ and binding constant was 9.37×10 5 .